PELUANG DAN TANTANGAN PENGEMBANG TEKNOLOGI PEMBELAJARAN JALUR INPASSING DI ERA DIGITAL - ENDANG SETYORINI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
Learning Technology Developer (PTP) is a functional learning technology position, a position that has the main scope of analyzing, planning, producing, implementing, controlling, and evaluating learning technology systems/models. PTP inpassing path is appointed based on elements of education, work experience, and years of service so that it has a heterogeneous level of capacity. One of the weaknesses of the adjustment/adjustment is that the level of position is only based on years of service and education without paying attention to the achievement of previous performance results, so that the PTP competencies that go beyond are not evenly distributed, some are still low and some are high/satisfactory. Therefore, it is necessary to increase competence and professional development. The purpose of this literature review is to obtain an overview of; (1) opportunities for increasing the competence and capacity of PTP as a career path, and (2) challenges in developing PTP competence and capacity in the field of learning, and technology as an effort to improve personal quality, (3) collaboration of PTP with other functional positions in supporting institutional performance . This study uses a descriptive method. The technique of collecting data and information is through literature study. The results of this study indicate that learning technology has opportunities and challenges in developing innovative ICT-based learning models, as well as collaboration between PTP developers and other functional positions in supporting institutional performance. ABSTRAKPengembang Teknologi Pembelajaran (PTP) adalah jabatan fungsional bidang teknologi pembelajaran, jabatan karir yang memiliki ruang lingkup tugas utama melakukan analisis dan pengkajian, perencanaan, produksi, penerapan, pengendalian, dan evaluasi terhadap sistem/model teknologi pembelajaran. PTP jalur inpassing diangkat berdasarkan unsur pendidikan, pengalaman kerja, dan masa kerja sehingga memiliki tingkat kapasitas yang heterogen. Salah satu kelemahan jalur penyesuaian/inpassing adalah penentuan jenjang jabatannya hanya didasarkan pada masa kerja dan pendidikan tanpa memperhatikan capaian hasil kinerja sebelumnya, sehingga kompetensi PTP jalur inpassing belum merata, ada yang masih rendah/kurang dan ada yang tinggi/memuaskan. Oleh sebab itu, diperlukan peningkatan kompetensi dan tuntutan pengembangan profesi. Tujuan kajian literatur ini adalah memperoleh gambaran mengenai; (1) peluang peningkatan kompetensi dan kapasitas PTP inpassing sebagai jabatan karir, dan (2) tantangan dalam mengembangkan kompetensi dan kapasitas PTP pada bidang pembelajaran, dan bidang teknologi sebagai upaya peningkatan kualitas pribadi, (3) kolaborasi PTP dengan jabatan fungsional lain dalam mendukung kinerja lembaga. Kajian ini menggunakan metode deskriptif. Teknik pengumpulan data dan informasinya melalui studi literatur. Hasil kajian literatur ini menunjukkan bahwa pengembang teknologi pembelajaran inpassing memiliki peluang dan tantangan dalam mengembangkan model pembelajaran inovatif berbasis TIK, serta kolaborasi PTP dengan jabatan fungsional lain dalam mendukung kinerja lembaga.